2014
DOI: 10.1021/ic502015c
|View full text |Cite
|
Sign up to set email alerts
|

Multimetallic Complexes and Functionalized Nanoparticles Based on Unsymmetrical Dithiocarbamate Ligands with Allyl and Propargyl Functionality

Abstract: Supporting Information (consisting of crystallographic data and anisotropic displacement ellipsoid plots for the structures of 6a and 11) are available on the WWW under http://.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Our interest in the surface functionalisation of gold nanoparticles (GNPs) with metal complexes began in 2008, [34] and since then much of our work [33][34][35][36][37][38] has focused on the use of dithiocarbamate (R 2 NCS 2 À )t ethers as an alternative to the ubiquitous thiol(ate) or disulfide attachment methodologies for GNPs. Competition experiments [38,39] have demonstrated that dithiocarbamates are able to displace thiol(ate)s from the surface of the nanoparticle, but not vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in the surface functionalisation of gold nanoparticles (GNPs) with metal complexes began in 2008, [34] and since then much of our work [33][34][35][36][37][38] has focused on the use of dithiocarbamate (R 2 NCS 2 À )t ethers as an alternative to the ubiquitous thiol(ate) or disulfide attachment methodologies for GNPs. Competition experiments [38,39] have demonstrated that dithiocarbamates are able to displace thiol(ate)s from the surface of the nanoparticle, but not vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2008, we have focused on the functionalisation of gold nanoparticles (GNPs) with transition metal units . Much of this work has focused on the use of dithiocarbamate (R 2 NCS 2 − ) tethers rather than the usual thiol(ate) or disulfide attachment methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2008, we have focusedo nt he functionalisation of gold nanoparticles (GNPs) with transition metal units. [14][15][16][17][18] Much of this work has focusedo nt he use of dithiocarbamate (R 2 NCS 2 À )tethers rather than the usual thiol(ate) or disulfide attachment methodologies. Competition experiments by us [19] and others [20] have shown that dithiocarbamates are able to displace thiol(ate)s from the surface of the nanoparticle, but not vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Although hydrophilic alkynes thus appear to be ideally suited to this study, the intrinsic nucleophilicity of their polar groups towards transition metals needs to be taken into account. Several studies have shown the preference of ruthenium and osmium triphenylphosphine hydride complexes to react with nucleophilic oxygen‐, nitrogen‐ and sulfur‐donor groups, even in the presence of terminal alkynes . Thus, when both functionalities are present on the same ligand, the alkyne insertion seems often to be less favoured compared to coordination of the other donors, especially when a bidentate chelate results …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the preferenceo fr uthenium and osmium triphenylphosphineh ydride complexes to react with nucleophilic oxygen-,n itrogen-and sulfur-donor groups,e ven in the presenceo ft erminal alkynes. [39,40] Thus, when both functionalities are present on the same ligand,t he alkyne insertions eems often to be less favouredc ompared to coordination of the other donors, especially when ab identate chelate results. [40,41] For theser easons, terminal alkynes were designed to possess hydrophilic properties combined with an absence of nucleophilic character.T he inexpensive 4-ethynylbenzyl alcohol was thus coupled to ap olyethylene glycol( PEG) chain via a simple esterification reaction.…”
Section: Detection Of Co In Cellsmentioning
confidence: 99%